PERFORMANCE EVALUATION OF BRAN SUPPLIERS WITH ANP AND OMAX METHODS - Rahmi Yuniarti; Ihwan Hamdala; Rangga Damar Bagaskara (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2017)
PT ASIMAS is an enterprise that cultivates and sells oyster mushrooms. One of the most crucial materials in the production of oyster mushrooms is bran. PT ASIMAS is currently facing several difficulties in performance evaluation of bran suppliers, such as no clear standards in the performance evaluation process of suppliers and late shipment of bran. The objectives of this research are to determine the proper criteria and subcriteria and provide improvement recommendation for the enterprise and bran suppliers. This research determines the weights of criteria and subcriteria with the Analytic Network Process (ANP). After that, the performance of bran suppliers is assessed through Scoring System with Objective Matrix (OMAX). The next step is evaluate the performance of suppliers with Traffic Light System. This research eventually resulted in 8 criteria and 14 subcriteria. The results of performance evaluation are as follows: Mr. Hariadi (4.9699), Mr. H. Zainal (4.3622), and Mr. Nur (4.0869). This research result also provides 14 improvement recommendations: 7 for the enterprise and 7 for bran suppliers.